Applications of density functional theory to corrosion and corrosion prevention of metals: A review - Dihao Chen; Wenjie Zhou; Yucheng Ji; Chaofang Dong (Materials Genome Engineering Advances)
Abstract Recently, density functional theory (DFT) has been a powerful tool to model the corrosion behaviors of materials, provide insights into the corrosion mechanisms, predict the corrosion performance of materials, and design the corrosion‐resistant alloys and organic inhibitors. DFT enables corrosion scientist to fundamentally understand the corrosion behaviors and corrosion mechanisms of materials from the perspective of atomic and electronic structures, combining with the traditional and advanced experimental tests. This review briefly summarizes the main features of DFT calculations and present a comprehensive overview of their typical applications to corrosion and corrosion prevention of metals, involving potential‐pH diagrams, hydrogen evolution reaction, anodic dissolution, passivity and passivity breakdown, and organic inhibitor for metals. The paper also reviews the correlations between DFT‐computed descriptors and the micro/macro physiochemical parameters of corrosion. Despite the great progress achieved by DFT, there are still some challenges in addressing corrosion issues due to the lack of bridges between the DFT‐calculated electronic parameters and the macro corrosion performance of materials. The DFT modeling‐experiment‐engineering‐theory model will be a potential method to clarify and build the links.